Besondere Punkte der Euler-Geraden - Giering, Oswald (Teaching Mathematics and Computer Science, 2005)
In the following article the concepts "Euler line of a triangle" and "radical centre of three circles" are connected. In this way we could find some relations between special points of a triangle (orthocentre H, centre of gravity S, circumcentreM, midpoint F of the nine-point circle) and the radical centres of special triples of circles.